The Determinants of Terrorist Shocks' Cross-Market Transmission - Konstantinos Drakos (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The determinants of the cross-market transmission mechanism for terrorist shocks are explored, focusing on two major terrorist events and 68 national stock markets. We generate daily abnormal returns from a three-factor world asset pricing model. Abnormal returns are then regressed on proxies of three transmission mechanisms; a world integration channel,a bilateral integration channel, and a liquidity channel. Our findings indicate that terrorism shocks are diffused cross-nationally, and moreover this diffusion is non-uniform. We find empirical support for all three channels when considered separately. The bilateral integration channel contains the highest explanatory power since we find that a third country's trade linkages with the "ground-zero" country explain about 24 % of the stock market reaction. A country's share in the world trade, a proxy for the world integration channel, is able to explain about 12 % of abnormal return variation, while the liquidity channel exhibits the lowest predictive power, with the value of stock trading explaining about 6 %. A hybrid model, were proxies for all channels are included, shows that only the bilateral trade linkages with the "ground-zero" country are significant determinants of the stock market reaction.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: F36; F32; G15; C21; C23; 330; Linkages; Stock Market Return; Terrorism